Analisis Kinerja Manajemen Konstruksi Menggunakan Pendekatan POAC Pada Proyek Rumah Sakit Garut - Fuja Purwanti; Ganjar Jojon Johari (Institut Teknologi Garut, 2026)
Construction management plays a crucial role in construction activities, particularly as the industry continues to grow rapidly. Construction management involves multidisciplinary organizations or individuals who systematically and measurably apply the POAC functions (Planning, Organizing, Actuating, and Controlling). This study aims to analyze the performance of construction management in the Intan Husada Hospital project in Garut Regency, West Java, using the POAC approach. Data were collected through questionnaires distributed to 30 respondents involved in the project. The results indicate that the Actuating factor has the highest influence with an average score of 3.40, followed by the Controlling factor with an average score of 3.38. These findings highlight the critical importance of effective implementation in improving construction management performance.